National rebirth as a pre-requisite for achieving goals of health sector reform: the role of health education (2007)
Government put in place reform agenda in health sector apparently to facilitate the achievement for all Nigerians a level of health that will permit them to lead a socially and economically productive live as enunciated in the National Policy on Health. However, the goal of the reform became difficult to achieve due to poor attitude of the people to National issues. There arose the need for national rebirth. The paper examined concepts of national rebirth, need for national rebirth efforts of government at National rebirth as well as health education. The paper noted that national rebirth programme embarked upon is laudable but lacks a force that could really do the magic of attitudinal change in the people. It therefore recommended the integration of health education into the National rebirth programme.